2018
DOI: 10.1371/journal.pone.0193713
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of depression and pain complaints among patients with cancer in a low income country

Abstract: BackgroundIn high income countries, cancer is one of the leading causes of death, with co-morbid depression contributing to the risk of increased mortality. However, both cancer and depression are neglected conditions in low income countries. The current study assessed the magnitude of depression and the association of pain complaints with depression among patients with cancer in a low income country.MethodIn this cross-sectional study participants were 390 patients with established diagnosis of cancer, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
6
21
3
1
Order By: Relevance
“…[19] The results revealed that the depression prevalence was higher than anxiety, as over two-thirds had depression (67.7%), and only half had anxiety (52.1%). These findings were similar to three studies: in China, the depression was a more significant psychological disorder among cancer patients than anxiety; [22] in Ethiopia the depression rate was 58.44%, higher than the anxiety rate of 51%; [23] and in Iran, the depression rate was 32% and anxiety 26.7%. [21] In contrast, two other studies used the HADS instrument and reported higher anxiety prevalence and lower depression levels among cancer patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[19] The results revealed that the depression prevalence was higher than anxiety, as over two-thirds had depression (67.7%), and only half had anxiety (52.1%). These findings were similar to three studies: in China, the depression was a more significant psychological disorder among cancer patients than anxiety; [22] in Ethiopia the depression rate was 58.44%, higher than the anxiety rate of 51%; [23] and in Iran, the depression rate was 32% and anxiety 26.7%. [21] In contrast, two other studies used the HADS instrument and reported higher anxiety prevalence and lower depression levels among cancer patients.…”
Section: Discussionsupporting
confidence: 89%
“…300 patients were interviewed from both the outpatient and inpatient department using The Aga Khan University Anxiety and Depression Scale (AKUADS) and a significant problem in a study in LMIC where cancer patients were four times more likely to suffer from a major depressive disorder. [22] Cancer stage was significantly associated with anxiety, and these results are similar to studies conducted in Indonesia, [29] and Portugal. [30] The current study revealed that depression had a significant association with treatment type, especially in cancer patients receiving chemotherapy (68.7%), similar to another study.…”
Section: Clinical and Cancer Factors Associated With Anxiety And Deprsupporting
confidence: 85%
“…The magnitude of depression in this study was consistent with other studies conducted among Chinese cancer patients (66.72%) [8] whereas this figure was higher than a study conducted in Addis Ababa [12], Iran [4] and meta-analysis done by Krebber et al [7]. This discrepancy could be attributable to the difference in the study populations in terms of types of cancer, the tool used for screening or other socio-demographic variations and severity of depression considered.…”
Section: Discussionsupporting
confidence: 87%
“…Cancer, the most stressful event that a person may experience often triggers depression [4,5]. The prevalence of depression among cancer exceeds that observed in the general population [6] and it ranges from 16.4% to 66.72% [4,[7][8][9][10][11][12]. Depression among cancer patients affects treatment since they have to take medications for both cancer and depression [4], affect acceptance of adjuvant cancer treatment [13], adherence [14] extend hospitalization, reduces the quality of life [15,16], and increases the risk of suicide [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted abroad have demonstrated a high rate of pain when the DART was used as a screening tool in cancer patients [6]. A cross-sectional study conducted by Alemayehu M et al [7] showed that the prevalence of moderate-to-severe depression in 390 cancer patients was 16.4% (95% CI: 13.1-20.4). In the current study, the incidence rates for self-reported depression and anxiety were 33.8% and 20.1%, respectively, in patients with moderate-to-severe pain.…”
Section: Discussionmentioning
confidence: 99%